2019
DOI: 10.1038/s41413-019-0045-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor 2α is a negative regulator of osteoblastogenesis and bone mass accrual

Abstract: Osteoblasts, which are the bone-forming cells, operate in a hypoxic environment. The transcription factors hypoxia-inducible factor-1α (HIF1) and HIF2 are key mediators of the cellular response to hypoxia. Both are expressed in osteoblasts. HIF1 is known to be a positive regulator of bone formation. Conversely, the role of HIF2 in the control osteoblast biology is still poorly understood. In this study, we used mouse genetics to demonstrate that HIF2 is an inhibitor of osteoblastogenesis and bone mass accrual.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 44 publications
(81 reference statements)
4
53
2
Order By: Relevance
“…Mechanistically, hypoxia has been shown to supress the RANKL decoy receptor, osteoprotegrin (OPG), preventing RANK-induced osteoclast formation and activity (Shirakura et al, 2010;Xian et al, 2016), although this has not been consistently demonstrated (Hulley et al, 2017;Kang et al, 2017;S. Y. Lee et al, 2019;Merceron et al, 2019;Shao et al, 2015;Wu et al, 2015). It is difficult to ascertain this inconsistency, but it may be explained by experimental variations of F I G U R E 1 HIF pathway activation.…”
Section: Osteoclastsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mechanistically, hypoxia has been shown to supress the RANKL decoy receptor, osteoprotegrin (OPG), preventing RANK-induced osteoclast formation and activity (Shirakura et al, 2010;Xian et al, 2016), although this has not been consistently demonstrated (Hulley et al, 2017;Kang et al, 2017;S. Y. Lee et al, 2019;Merceron et al, 2019;Shao et al, 2015;Wu et al, 2015). It is difficult to ascertain this inconsistency, but it may be explained by experimental variations of F I G U R E 1 HIF pathway activation.…”
Section: Osteoclastsmentioning
confidence: 99%
“…However, it has recently been reported that HIF-2 is a negative regulator of osteoblastogenesis (S. Y. Lee et al, 2019;Merceron et al, 2019). Deficiency of HIF-2 increases bone mass through promoting osteoblast differentiation and inhibiting osteoclast differentiation (Merceron et al, 2019).…”
Section: Osteoblastsmentioning
confidence: 99%
See 3 more Smart Citations